Correlation between Spiritual Well-Being and Level of Fatigue among Patients Suffering from Breast Cancer - Maria Komariah; Mohd Khairul Zul Hasymi Firdaus; Kalpana Paudel Aryal; Md Abdul Latif (Jurnal Keperawatan Padjadjaran, 2021)
Cancer-related fatigue has been shown to be a significant side effect that influences a person’s wellbeing, during treatment, and after treatment. It is recorded that cancer patients have also been shown experiencing spiritual distress. The study aims to determine the connection between spiritual well-being and cancer-related fatigue among patients suffering from breast cancer during chemotherapy treatment. 112 patients who were undergoing chemotherapy treatment were recruited in this study using a correlational design. The instruments used in assessing spiritual well-being and fatigue are Functional Assessment of Chronic Illness Therapy - Spirituality (FACIT-Sp) and FACIT-Fatigue Scales. Data were analyzed using the Spearman Correlation analysis. Mean spiritual well-being score was 35.91 (SD = 6.89), and the mean fatigue score was 33.04 (SD = 9.58). There were a moderate and significant correlation between fatigue scores and spiritual well-being (r = .364, p < 0.001). Breast cancer patients who had higher spiritual well-being that means they would alleviate fatigue symptoms. Therefore, nurses should consider that increasing spiritual well-being would reduce fatigue and vice versa.